Image enhancement and segmentation using dark stretching technique for Plasmodium Falciparum for thick blood smear - N. S. M. M., Hanif (The Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org